2021
DOI: 10.1186/s13027-021-00387-y
|View full text |Cite
|
Sign up to set email alerts
|

Re-thinking treatment strategies for febrile neutropenia in paediatric oncology population: the perspective from a developing country

Abstract: Background This study was conducted to evaluate the microbiological profile of bacterial isolates in febrile neutropenia in a pediatric oncology unit, thereby, reviewing the use of restricted antibiotics and need for aggressive medical treatment accordingly. Methods A prospective observational study was conducted in a paediatric haemat-oncology division of a tertiary care teaching hospital in southern India from September 2014 to August 2016. One h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…However, in clinical settings, when the amount of blood drawn simultaneously from peripheral and CVC culture is not equal and semiquantitative and quantitative cultures are not routinely performed, this information is not available and the decision on whether or not to remove the catheter is mostly based on patient's clinical condition and response to therapy. 23 Most of the pathogens isolated in our cohort (51.4%) were gram-negative bacteria similar to recent reports of fever and neutropenia in adult and pediatric patients outside the United States (east Asia and Europe) 24,25 but in contrast to studies from the United States and France in which most of the isolates were gram-positive mainly viridans group streptococci and CONS. 26,27 In addition, the growing resistance (especially among gram-negative bacteria) in oncology children as seen in our cohort (35.1% of ESBL phenotype among Enterobacteriaceae spp.)…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in clinical settings, when the amount of blood drawn simultaneously from peripheral and CVC culture is not equal and semiquantitative and quantitative cultures are not routinely performed, this information is not available and the decision on whether or not to remove the catheter is mostly based on patient's clinical condition and response to therapy. 23 Most of the pathogens isolated in our cohort (51.4%) were gram-negative bacteria similar to recent reports of fever and neutropenia in adult and pediatric patients outside the United States (east Asia and Europe) 24,25 but in contrast to studies from the United States and France in which most of the isolates were gram-positive mainly viridans group streptococci and CONS. 26,27 In addition, the growing resistance (especially among gram-negative bacteria) in oncology children as seen in our cohort (35.1% of ESBL phenotype among Enterobacteriaceae spp.)…”
Section: Discussionsupporting
confidence: 88%
“…Most of the pathogens isolated in our cohort (51.4%) were gram-negative bacteria similar to recent reports of fever and neutropenia in adult and pediatric patients outside the United States (east Asia and Europe) 24,25 but in contrast to studies from the United States and France in which most of the isolates were gram-positive mainly viridans group streptococci and CONS 26,27 . In addition, the growing resistance (especially among gram-negative bacteria) in oncology children as seen in our cohort (35.1% of ESBL phenotype among Enterobacteriaceae spp.)…”
Section: Discussionsupporting
confidence: 87%
“…A summary of the study characteristics is shown in Figure 2. The included studies were from diverse regions globally, with six (18%) conducted in the United States 2,11–15 and 28 (82%) studies in other countries (Africa, n = 1 [3%]; Asia, n = 15 [44%]; Oceania, n = 2 [6%]; Europe, n = 4 [12%]; Middle East, n = 4 [12%]; Central America, n = 1 [3%]; South America, n = 1 [3%]) 16–43 (Figure S2). Majority ( n = 21, 62%) 2,11,12,16,18,19,21,25,26,28–35,38,39,42,43 of studies utilized standard culture methods, while a smaller number ( n = 8, 24%) 13,14,20,22–24,27,41 of studies reported on newer methods such as metagenomic sequencing and PCR diagnostics (i.e., qPCR [including singleplex and multiplex], 22,23 panfungal real‐time PCR, 27 16S rRNA gene PCR, 23,24 respiratory viral panel PCR, 13,20,41 and Pneumocystis jirovecii PCR 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were from diverse regions globally, with six (18%) conducted in the United States 2,11–15 and 28 (82%) studies in other countries (Africa, n = 1 [3%]; Asia, n = 15 [44%]; Oceania, n = 2 [6%]; Europe, n = 4 [12%]; Middle East, n = 4 [12%]; Central America, n = 1 [3%]; South America, n = 1 [3%]) 16–43 (Figure S2). Majority ( n = 21, 62%) 2,11,12,16,18,19,21,25,26,28–35,38,39,42,43 of studies utilized standard culture methods, while a smaller number ( n = 8, 24%) 13,14,20,22–24,27,41 of studies reported on newer methods such as metagenomic sequencing and PCR diagnostics (i.e., qPCR [including singleplex and multiplex], 22,23 panfungal real‐time PCR, 27 16S rRNA gene PCR, 23,24 respiratory viral panel PCR, 13,20,41 and Pneumocystis jirovecii PCR 20 ). Other assessed tests or studies included histopathology examination, 15 Aspergillus galactomannan antigen assay (GM), 15,17,20,27 (1‐3)‐β‐D‐glucan assay (BDG), 15,27 and procalcitonin and C‐reactive protein biomarkers 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation